Impact of image reconstruction parameters when using 3D DSA reconstructions to measure intracranial aneurysms. (6th April 2017) - Ruedinger, Katrina L; Rutkowski, David R; Schafer, Sebastian; Roldán-Alzate, Alejandro; Oberstar, Erick L; Strother, Charles
Abstract : Background and purpose: Safe and effective use of newly developed devices for aneurysm treatment requires the ability to make accurate measurements in the angiographic suite. Our purpose was to determine the parameters that optimize the geometric accuracy of three-dimensional (3D) vascular reconstructions. Methods: An in vitro flow model consisting of a peristaltic pump, plastic tubing, and 3D printed patient-specific aneurysm models was used to simulate blood flow in an intracranial aneurysm. Flow rates were adjusted to match values reported in the literature for the internal carotid artery. 3D digital subtraction angiography acquisitions were obtained using a commercially available biplane angiographic system. Reconstructions were done using Edge Enhancement (EE) or Hounsfield Unit (HU) kernels and a Normal or Smooth image characteristic. Reconstructed images were analyzed using the vendor's aneurysm analysis tool. Ground truth measurements were derived from metrological scans of the models with a microCT. Aneurysm volume, surface area, dome height, minimum and maximum ostium diameter were determined for the five models. Results: In all cases, measurements made with the EE kernel most closely matched ground truth values. Differences in values derived from reconstructions displayed with Smooth or Normal image characteristics were small and had only little impact on the geometric parameters considered. Conclusions: Reconstruction parameters impact the accuracy of measurements made using the aneurysm analysis tool of a commercially available angiographic system. Absolute differences between measurements made using reconstruction parameters determined as optimal in this study were, overall, very small. The significance of these differences, if any, will depend on the details of each individual case.